PEMBERIAN KALIUM PADA TANAH GAMBUT TERHADAP PRODUKSI, VIABILITAS, DAN VIGOR BENIH BEBERAPA VARIETAS KACANG TANAH - T. Sarwanidas; Syamsuddin Syamsuddin; Teti Arabia (Jurnal Floratek, 2014)
The research was aimed at finding out the relationship between potassium dosages on peats soil, yield, seedvigor, and viability of peanut. The experiment was arranged ina completely randomized design (CRD), factorial 5 x 4 with 3 replications. Potassium application was consisted of 5 levels: 0 kg ha-1, 25 kg ha-1, 50 kg ha-1,  75 kg ha-1, and 100 kg ha-1. Variety was consisted of  4 levels :  Naga Umbang, Jerapah, Gajah  and  Bison. Variables observed were yield, seed vigor, and seed viability. Results showed that potassium did not exert significant effects on all variables observed, except  on seed vigor and viability.  Varieties significantly affected yield, where Bison provided the best dried pod weight and Jerapah gave the best seed vigor and viability. No significant interaction existed between varieties and dosage of K fertilizer on the peanut yield, seed vigor, and seed viability.